A bag of marbles - Kris, 1972-; Bailly, Vincent; Gauvin, Edward; Joffo, Joseph (Minneapolis : Graphic Universe, 2013)
In 1941, ten-year-old Joseph Joffo and his older brother, Maurice, must hide their Jewish heritage and undertake a long and dangerous journey from Nazi-occupied Paris to reach their other brothers in the free zone.
Translated from the French.
Translation of: Sac de billes.
Young Adult.
Young Adult
Keywords: Joffo, Joseph -- Comic books, strips, etc. -- Juvenile literature; Joffo, Maurice -- Comic books, strips, etc. -- Juvenile literature; Joffo, Joseph -- Cartoons and comics; Joffo, Maurice -- Cartoons and comics; Joffo, Joseph -- Comic books, strips, etc; Joffo, Maurice -- Comic books, strips, etc; Holocaust, Jewish (1939-1945) -- France -- Comic books, strips, etc -- Juvenile literature; Jews -- France -- Comic books, strips, etc -- Juvenile literature; World War, 1939-1945 -- France -- Comic books, strips, etc -- Juvenile literature; Cartoons and comics; Holocaust, Jewish (1939-1945) -- France -- Cartoons and comics; Jews -- France -- Cartoons and comics; World War, 1939-1945 -- France -- Cartoons and comics; Comic books, strips, etc; Holocaust, 1939-1945 -- Comic books, strips, etc; Jews -- France -- Comic books, strips, etc; World War, 1939-1945 -- France -- Comic books, strips, etc; France -- History -- German occupation, 1940-1945 -- Comic books, strips, etc -- Juvenile literature; France -- History -- German occupation, 1940-1945 -- Cartoons and comics; France -- History -- 1940-1945, German occupation -- Comic books, strips, etc